A histo-morphometric study on the developing gastrointestinal tract of the axolotl, Ambystoma mexicanum - Badawy, Gamal M. (JOURNAL OF ADVANCES IN BIOLOGY, 2014)
The histological structure of the developing gastrointestinal tract (GIT) of the axolotl, Ambystoma mexicanum, was investigated during embryonic, larval and juvenile stages. The earliest histological events witnessed the formation of the archenteron as a more or less circular shaped cavity at stage 13. Concurrent with the first significant elongation of the embryo, the gut was evidently subdivided into foregut, midgut and hindgut at stage 16 after which there was a progressive but slow differentiation up to stage 37. Very active cellular movements occurred and resulted in the anatomical differentiation of the stomach at stage 40. During the endogenous feeding phase, two prominent features characterized the histological structure of the developing GIT. Firstly, the endodermal yolk mass resorption which occurred in a proximodistal (PD) direction and lasted up to six days after hatching. Secondly, the progressive PD cellular differentiation during which both the endodermal and mesodermal components showed a co-ordinated and concomitant histological differentiation towards the establishment of the gastrointestinal wall. Subsequent stages displayed active cellular proliferation accompanied with progressive histogenesis, which eventually led to a well-developed GIT in the 2.5 cm long larvae. The histological structure of the mature GIT is described and illustrated. Furthermore, certain morphometric parameters were measured during development.